Attitude of Social Studies Teachers towards the Utilization of Computers Classroom Instruction in Kogi State: The Role of School Location and Gender - Shaibu, Joshua Shaka; Ogunbiyi, Joseph Olukayode; Shuaibu, Kennedy; Anum, Obinna; Tolorunleke, Emmanuel Adebayo; Ajibili, Ocheje; Atawodi, Ibrahim; Edoh, Monday; Ochoji, Audu David; Akor, Mohammed Sule; Suleiman, Beulah Dukanwojo; Ilemona, Rose; Ochimana, Anyaja; Musa, Hadiza A (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2023)
The study examined the Attitude of Social Studies Teachers towards the Utilization of Computers Classroom Instruction in Kogi State: The role of School location and gender was considered. A total of 280 schools out of 290 schools constitute the study. The study adopted a survey design to elicit information with a target population comprising 427 Social Studies teachers in Kogi State. Random sampling technique was used to select a sample size of 427(224 male and 203 female Social Studies teachers from secondary schools offering Social Studies) in Kogi state. Two research questions were raised and two null hypotheses was formulated and tested. The instrument for data collection was Teachers Computer Attitude and Utilization Scale (TCAUSQ) made up of 22 items and was validated. The reliability index of 0.78 was obtained. Mean and standard deviation was used to answer the research questions, while t-test was used to test the hypotheses at 0.05 level of significance. The study revealed that Male Social Studies teachers have higher negative attitude towards the use of computer than their female counterparts. However, no significant difference was established between male and female Social Studies teachers on the use of computer. It was recommended among others that there should be periodic state government sponsored in-service training for teachers towards the use of computer as a tool for instruction in the teaching and learning of Social Studies, collaborative action and participation of government and non-governmental organization towards enhancing teacher’s attitude towards computer usage and all secondary schools Social Studies department in Nigeria, most especially in Kogi State should be furnished with computers, computer laboratories and sustainable electric power supply to enhance the use of computer as an instructional tool in Nigerian schools.